Training in Caring: A Practical Program for Sixth and Seventh Graders with Pre-schoolersqB - Allan, John A. B. (Canadian Journal of Counselling and Psychotherapy, 2012)
This paper describes the training of sixth and seventh graders in helping with preschoolers. So far 230 students have been involved in three 2 1/2 hour play sessions. After helping, students filled in observation forms and met with the writer for a half-hour discussion and feedback. The training concentrated on helping them understand normal development, the concept of developmental stages, on self-awareness and the learning of communication skills to facilitate caring and interaction with young children.